Pembelajaran Konsep Dasar Mewarnai pada Anak Autis - Citrawati Rochmah Dewi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research is motivated by the lack of ability in learning, communicating, and social interaction for children with autism. In this case appropriate techniques and methods are needed in providing learning to autistic children. Learning the basic concepts of coloring is stated to be important to learn for children, including children with autism. Several studies have stated that learning the basic concepts of coloring can affect fine motor development for children with autism. This study aims to determine the learning planning of the basic concept of coloring in children with autism. In addition, this study also aims to determine the effect and effectiveness of this learning for autistic children. The type of research used is descriptive qualitative research, the method used is literature study. The research focuses on analyzing previous studies related to the objectives of this study. The results of the study show that learning the basic concepts of coloring is important to be applied to autistic children. Then from some of the summaries obtained by the author, data related to the activities of recognizing colors in learning carried out by several researchers included explaining colors, grouping colors, matching colors, and using basic colors in coloring. Based on this, the results obtained are that the basic concept of coloring activities has an effect on autistic children, in each learning activity autistic children do not feel bored in learning. Apart from that, with the planning carried out, this has a positive effect on children with autism, this can be seen by the fact that most autistic children are able to recognize colors and are able to apply basic colors in coloring.